Assessing the Influence of Water Management and Rainfall Seasonality on Water Quality and Intestinal Parasitism in Rural Northeastern Brazil - Alexandre Pessoa Dias; Deiviane Calegar; Filipe Anibal Carvalho-Costa; Maria de Fátima Leal Alencar; Caroline Ferraz Ignacio; Milena Enderson Chagas da Silva; Antonio Henrique Almeida de Moraes Neto (Journal of Tropical Medicine)
Introduction. The drought in the Brazilian semiarid region has affected the quality of water. This study assessed the relationships between enteric parasitoses, water management, and water quality, correlating them with pluviometric seasonality. Methods. Cross-sectional surveys were carried out in four rural communities at the beginning of the dry season (n=151), at the end of the dry season (n=184), and in the rainy season (n=199), in order to collect sociodemographic data, human fecal samples, and samples of the water used for human consumption for physicochemical and microbiological analyses. In 2015, water filters were provided to 30 households under study. Results. There was an increasing trend in detection rates of commensal protozoa and the Entamoeba histolytica/Entamoeba dispar complex at the beginning of the rainy season, with detection rates of 6% in 2014 and 21.6% in 2016. Giardia intestinalis and Ascaris lumbricoides presented distinct temporal distributions, which peaked in 2015: 20.1% and 30%, respectively. The proportion of inhabitants drinking inadequate water was 55% at the beginning of the dry season and 28.8% at the end of the dry season, reaching 70.9% at the beginning of the rainy season. The presence of filters reduced this proportion among those who received the hollow ceramic candle filter. Conclusions. Data suggest that the strategies to increase water supply in the Brazilian semiarid region can be ameliorated in order to improve the quality of drinking water.